Carbamylated LL-37 as a modulator of the immune response. Issue 3 (April 2016) - Koro, Catalin; Hellvard, Annelie; Delaleu, Nicolas; Binder, Veronika; Scavenius, Carsten; Bergum, Brith; Główczyk, Izabela; Roberts, Helen M; Chapple, Iain LC; Grant, Melissa M; Rapala-Kozik, Maria; Klaga, Kinga; et al.
Carbamylation of lysine residues and protein N -termini is an ubiquitous, non-enzymatic post-translational modification. Carbamylation at sites of inflammation is due to cyanate formation during the neutrophil oxidative burst and may target lysine residues within the antimicrobial peptide LL-37. The bactericidal and immunomodulatory properties of LL-37 depend on its secondary structure and cationic nature, which are conferred by arginine and lysine residues. Therefore, carbamylation may affect the biological functions of LL-37. The present study examined the kinetics and pattern of LL-37 carbamylation to investigate how this modification affects the bactericidal, cytotoxic and immunomodulatory function of the peptide. The results indicated that LL-37 undergoes rapid modification in the presence of physiological concentrations of cyanate, yielding a spectrum of diverse carbamylated peptides. Mass spectrometry analyses revealed that the N -terminal amino group of Leu-1 was highly reactive and was modified almost instantly by cyanate to generate the predominant form of the modified peptide, named LL-37 C1 . This was followed by the sequential carbamylation of Lys-8, Lys-12, and Lys-15 to yield LL-37 C8, and Lys-15 to yield LL-37 C12, 15 . Carbamylation had profound and diverse effects on the structure and biological properties of LL-37. In some cases, anti-inflammatory LL-37 was rapidly converted to pro-inflammatory LL-37.